Assessing the Impact of Lymphedema Therapy Referral on Breast Cancer Survivors’ Lymphedema Knowledge: A Cross-Sectional Survey - Madelyn Klugman; Yashasvini Sampathkumar; Sujata Patil; Kathryn R. Tringale; Giacomo Montagna; Jackie Finik; Ting-Ting Kuo; Carolyn Eberle; Alexandr Pinkhasov; Theresa Gillis; Francesca Gany; Victoria Blinder (BMC Women's Health)
Abstract Background Lymphedema is a common problem that adversely impacts quality of life in breast cancer survivors. Although lymphedema risk is modifiable through behavior change, there is no standardized approach to educate survivors about risk-lowering strategies. Furthermore, misconceptions about lymphedema risk factors and risk-lowering strategies are common. The aim of this study was to evaluate the effect of lymphedema therapy referral on knowledge about lymphedema risk. Methods This was a cross-sectional single institution study in which breast cancer survivors at a National Cancer Institute-designated cancer center completed an anonymous questionnaire between 2014 and 2015. Eligibility criteria were age ≥ 18, female sex, English-speaking, > 6 months post definitive breast cancer surgery, no cancer recurrence, and no prior or subsequent second cancer. The questionnaire included sociodemographic variables, clinical factors including prior lymphedema therapy referral, and 10 true/false questions assessing knowledge about lymphedema risk. Multivariable logistic regression analyses assessed the relationship between prior lymphedema therapy referral and correctly answering questions about lymphedema risk. Results Of 209 participants, 53 (25%) had been referred to lymphedema therapy. Those who had undergone sentinel lymph node biopsy were less frequently referred to lymphedema therapy [15 (14%)] than those who had undergone axillary lymph node dissection [38 (39%)]. Five of the true/false questions had a correct response rate of < 80%. After controlling for age, race/ethnicity, education, type of axillary surgery, and receipt of radiation therapy, referral for lymphedema therapy was associated with correctly answering two questions about lymphedema: weight gain increases lymphedema risk [odds ratio, 95% confidence interval: 3.63 (1.66–7.96)] and patients are recommended to exercise their arm on an airplane [2.65 (1.15–6.13)]. Conclusions Misconceptions about lymphedema prevention and management are common among breast cancer survivors. Lymphedema therapy referral is a potential opportunity to debunk misunderstandings and educate at-risk patients regarding lymphedema.